Electronic global-shutter one-thin-film-transistor active pixel sensor array with a pixel pitch of 50 μm and photoconductive gain greater than 100 for large-area dynamic imaging - Hu, Yunfeng; Xu, Yangbing; Liu, Jinming; Qi, Yihong; Wang, Kai (Frontiers in Physics, 2022)
In large-area dynamic imaging, an active pixel sensor (APS) is proposed. However, there is a trade-off between signal-to-noise ratio (SNR) and spatial resolution. To resolve this, a 256×256 active pixel image sensor array based on a 3-D dual-gate photosensitive thin-film transistor (TFT) is presented in this work, with a pixel pitch of 50 μm, pixel fill factor of 63%, photoconductive gain of 102 ~ 104 and spatial resolution of 505 ppi. An electronic global shutter is enabled by dual-gate biasing without additional a shutter TFT. Such an array is capable of dynamic imaging at a frame rate of 34 Hz.